Interleukin-17A mRNA Expression is Associated with the Prognosis of Patients with Colorectal Cancer: A Pooled Meta-Analysis - Wei Yang; Jiejing Chen; Hailiang Liang; Wei Wu (Turkish Journal of Gastroenterology, 2022)
Background: Interleukin-17A is a proinflammatory cytokine that is produced by TH17 cells, and plays a dual role in tumor progression, infectious diseases, and autoimmune disorders. Interleukin-17A is induced during colorectal tumorigenesis and angiogenesis, although some studies have reported an anti-tumor effect as well. The aim of our study was to assess the prognostic role of interleukin-17A in colorectal cancer and determine the potential mechanisms. Methods: The GEO database was searched using the keyword “colorectal cancer”, and 10 datasets were identified that included interleukin-17A mRNA expression and survival data of several colorectal cancer patient cohorts. The patients were stratified into the interleukin-17Ahigh and interleukin-17Alow groups based on the median expression level. Results: Higher interleukin-17A mRNA levels were associated with better overall survival rates and the early tumor stage, indicating a protective role of interleukin-17A in colorectal cancer. Furthermore, interleukin-17A mRNA expression also correlated positively with that of TNFS11, CCR6, and CCL20, indicating that the anti-tumor effect of interleukin-17A is likely mediated by enhancing tumor antigen presentation by dendritic cells and recruiting the activated tumor-specific CD8+ cytotoxic T lymphocytes. The IL-23 and STAT3 mRNA levels were also significantly higher in the interleukin-17Ahigh group, which points to an upstream regulatory role of IL-23/STAT3 axis. Finally, the immune checkpoints PDCD1 (PD-1) and CD274 (PDL-1) were also positively correlated with interleukin-17A mRNA expression, indicating that interleukin-17A is a promising predictor of the immunotherapeutic outcome of PD-1/PDL-1 blockade in colorectal cancer. Conclusion: Interleukin-17A mRNA is a protective factor in colorectal cancer and a promising biomarker for assessing the prognosis and immunotherapeutic response Cite this article as: Yang W, Chen J, Liang H, Wu W. Interleukin-17A mRNA expression is associated with the prognosis of patients with colorectal cancer: A pooled meta-analysis. Turk J Gastroenterol. 2022;33(12):995-1003.